2020
DOI: 10.1108/ejm-06-2019-0546
|View full text |Cite
|
Sign up to set email alerts
|

The allure of starting afresh: the effects of mortality-related sadness on the effectiveness of fresh start appeals

Abstract: Purpose This paper aims to examine how mortality-related sadness, as compared to other emotions such as fear, anger and happiness, can leverage the effectiveness of fresh start appeals. Design/methodology/approach Drawing upon the consumption-based affect regulation principle, this paper investigates how sadness associated with mortality can elicit the appraisal of irretrievable loss, which subsequently increases the effectiveness of fresh start appeals. These predictions are tested across three experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Finally, further research should address the relationship between emotional temperature and other underlying emotional appraisals such as uncertainty, legitimacy/fairness and goal consistency as well as its effect on marketing outcomes (Klein and Melnyk, 2016; Septianto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further research should address the relationship between emotional temperature and other underlying emotional appraisals such as uncertainty, legitimacy/fairness and goal consistency as well as its effect on marketing outcomes (Klein and Melnyk, 2016; Septianto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…moderators have been less studied in extant research. Notwithstanding that scarcity,Septianto et al (2021) found that individual differences in the extent to which emotional states are perceived as malleable can moderate the effect of anger on the evaluation of specific affect regulation appeal. They found that individuals with…”
mentioning
confidence: 89%
“…Moreover, certain contextual factors, such as temporal focus, can increase self-regulation across positive emotions (Winterich & Haws, 2011). Similarly, malleable belief and process accountability can yield similar behaviour across negative emotions (Garg et al, 2017;Septianto et al, 2021).…”
Section: Differences and Similarities Across Emotionsmentioning
confidence: 99%
See 2 more Smart Citations